Effective Communication to Support Inpatient Service Innovation: Room Available Without Added Cost (KT3B) Program at Mardi Rahayu Hospital - Dian Ratnawati (Journal La Sociale, 2024)
Communication is needed in an organization to overcome various problems that exist. Problems that arise usually greatly affect the quality of service to the public. Improving service quality is not only the addition of service variables, but can be done through improvements to previously running services. Innovation in the health service industry is an obligation that is carried out. Efforts to improve access to health services for patients are a priority that is presented in services in all health facilities. Efforts to build Mardi Rahayu Hospital's effective communication strategy to support inpatient service innovation which is a priority inpatient program. This research uses descriptive qualitative methodology belonging to (Moleong, 2012) by trying to reveal what effective communication strategies are used in launching inpatient service innovations. Data collection was carried out by interviewing registration officers, and nurses who became the primary data of researchers, and also direct observation.